2011
DOI: 10.1111/j.1600-0412.2011.01237.x
|View full text |Cite
|
Sign up to set email alerts
|

Scalp blood lactate for intra‐partum assessment of fetal metabolic acidosis

Abstract: In the case of a non-reassuring fetal heart rate, fetal scalp blood lactate provides more accurate information on fetal acid-base status than does pH and/or BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 31 publications
5
36
0
Order By: Relevance
“…Growing evidence [8,12,13,22] is suggesting a replacement of pH levels by lactate for predicting fetal acidosis in fetal scalp blood and cord blood samples. This approach is attractive because metabolic acidosis, which is predicted more accurately by lactate than by pH, causes more long-term damage to the fetus than respiratory distress, which is indicated by decreased pH levels.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Growing evidence [8,12,13,22] is suggesting a replacement of pH levels by lactate for predicting fetal acidosis in fetal scalp blood and cord blood samples. This approach is attractive because metabolic acidosis, which is predicted more accurately by lactate than by pH, causes more long-term damage to the fetus than respiratory distress, which is indicated by decreased pH levels.…”
Section: Discussionmentioning
confidence: 98%
“…Fetal scalp pH measurement is more difficult to perform than fetal lactate testing, needs a longer collection and analyzing time and has a higher sample collection failure rate due to sample volume limitations [6,7,9,10]. Furthermore, recent studies have indicated that lactate may provide superior diagnostic reliability for early detection of fetal hypoxia than pH [11][12][13]. Furthermore, a close correlation between pH values, lactate concentrations, and neonatal outcome has been reported [6,7,10,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The use of FBS varies largely between countries, with reported frequencies between 3 and 15% in some countries [1,19,20], and essentially none in other. The attitude toward the use of FBS can be considered liberal at the labor ward where this study was conducted, with a frequency of 11% of all labors, but is comparable to other countries where FBS is a part of intrapartum fetal surveillance routines [19].…”
Section: Commentsmentioning
confidence: 98%
“…The attitude toward the use of FBS can be considered liberal at the labor ward where this study was conducted, with a frequency of 11% of all labors, but is comparable to other countries where FBS is a part of intrapartum fetal surveillance routines [19].…”
Section: Commentsmentioning
confidence: 99%